2021
DOI: 10.3389/fpsyg.2021.661172
|View full text |Cite
|
Sign up to set email alerts
|

Explorations in Reported Moral Behaviors, Values, and Moral Emotions in Four Countries

Abstract: University students (n = 758) from Bulgaria, Estonia, Finland, and Portugal were given a list of morally relevant behaviors (MRB), the Schwartz Value Survey (PVQ40) and Tangney’s TOSCA, measuring empathic guilt, guilt over norm-breaking, and shame. A factor analysis of MRB yielded 4 dimensions: prosocial behaviors, interpersonal transgressions, antisocial behaviors and secret transgressions. Prosocial behaviors were predicted by self-transcendence–self-enhancement (SET) value contrast only while the three tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(81 reference statements)
1
2
0
Order By: Relevance
“…Subgroup analyses detecting sources of heterogeneity revealed differences with regard to the continents. These results are in line with the findings of other studies that have already found cultural differences regarding morality (Cowell et al, 2017;Myyry et al, 2021;Sachdeva et al, 2011). These differences should be considered in future analyses.…”
Section: Discussionsupporting
confidence: 92%
“…Subgroup analyses detecting sources of heterogeneity revealed differences with regard to the continents. These results are in line with the findings of other studies that have already found cultural differences regarding morality (Cowell et al, 2017;Myyry et al, 2021;Sachdeva et al, 2011). These differences should be considered in future analyses.…”
Section: Discussionsupporting
confidence: 92%
“…. In line with the aforementioned assertions, numerous studies have discovered that prosociality in young adults is significantly correlated with having higher levels of self-transcendence values than prosociality with any other value including: hedonism, stimulation, self-direction, achievement, and power (Abramson et al, 2018;Danioni & Barni, 2019Kesberg & Keller, 2021;Lee & Cho, 2019;Leijen et al, 2022;Myyry et al, 2021;Saroglou et al, 2020;Vecchione et al, 2019).…”
mentioning
confidence: 68%
“…Based on the 10 values of the values theory (Schwartz, 1969), circular interactive changes (Myyry, 2021), and the above research hypotheses, we propose the following research framework (Figure 1).…”
Section: College Studentsmentioning
confidence: 99%